Does advertising really work?: The direct stimulating and attention-grabbing effects of advertising on investor behavior. Issue 3 (16th March 2020) - Wu, Keke; Yu, Yan; Dong, Dayong
Abstract : Purpose: This paper aims to examine the direct and indirect effects of advertising on investor behavior. Design/methodology/approach: The authors use a novel and direct measure of investor attention: the number of investors whose watch lists has the stock. Findings: The authors find that beyond its direct effect through information dissemination, advertising has an indirect effect with regard to grabbing investor attention and the trading response. The authors further find that an increase in attention induces a positive influence on the impact of advertising on investor behavior. Originality/value: First, it complements studies of home bias, in which investors are more likely to buy familiar stocks. Second, it also complements the literature on advertising and investor attention and on attention and capital markets. Third, with a new and unambiguous measure of investor attention. Fourth, combining the direct and indirect aspects, this study presents a detailed description of the financial market effect of advertising.